The Effect of Breast Care Intervention on the Incidence of Breast Engorgement among Postpartum Women - Nuryana, Riska; Sumarmi; Mantasia; Dewi S; Alwi; Mardiana (Omni Health Journal, 2025)
Background: After childbirth, the problem that is often experienced by postpartum mothers is breast milk (engorgement), This may be caused by an anomaly of the mamma's papillae, limited lactoferous ducts, or insufficient emptying of the glands. Objective: To determine the relationship between postpartum breast care interventions and the prevalence of breastfeeding dams at the Baruga Health Center, Bantaeng Regency. Methods: This study used a cross-sectional descriptive survey methodology. Looking for an overview of breast care interventions in postpartum mothers with breastfeeding dams at the Baruga Health Center, Bantaeng Regency. Results: It showed that 13 respondents (86.0%) did not do breast care and experienced breast clotting, 1 respondent (7.0%) had done breast care and experienced breast clotting, 2 respondents (14.0%) did not do breast care and did not experience breast clotting. froze breast milk, and 14 respondents (94.0%) did not do breast care and froze breast milk. Conclusion: For the breastfeeding process to be successful, the breasts must receive frequent attention. Ensuring adequate milk production throughout the breastfeeding period, preventing breast abnormalities, and maintaining breast health during the breastfeeding process are the goals